2019
DOI: 10.1177/1043454219835448
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Nurse Managers’ Perceptions of Palliative Care and End-of-Life Communication

Abstract: Annually, more than 13,000 children younger than 20 years (Compas, Jaser, Dunn, & Rodriguez, 2012) are diagnosed with cancer, and approximately 40,000 children are receiving cancer treatments (Compas et al., 2014). Despite advances in cancer therapy and improvements in overall survival rates during the past decades, children still die from cancer. Approximately 20% of all children diagnosed with cancer will not survive 5 years or more (American Cancer Society, 2016; Field & Behrman, 2003; Knobf, 2013). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
(31 reference statements)
0
10
0
12
Order By: Relevance
“…This ultimately results in anxiety and job dissatisfaction. Concurrent with this finding, previous studies reported, a stressful work environment, increased rate of a medication error and decreased quality of care provided to patients [35,36]. Some studies have highlighted that in Egypt, nurses and pharmacists were exposed to hazardous drugs for cancer treatment, and also in Iran, nurses showed changes in their mitochondrial parameters and there was cytotoxicity of their lymphocytes due to exposure to chemotherapy inhalation [5,13].…”
Section: Discussionmentioning
confidence: 72%
“…This ultimately results in anxiety and job dissatisfaction. Concurrent with this finding, previous studies reported, a stressful work environment, increased rate of a medication error and decreased quality of care provided to patients [35,36]. Some studies have highlighted that in Egypt, nurses and pharmacists were exposed to hazardous drugs for cancer treatment, and also in Iran, nurses showed changes in their mitochondrial parameters and there was cytotoxicity of their lymphocytes due to exposure to chemotherapy inhalation [5,13].…”
Section: Discussionmentioning
confidence: 72%
“…This ultimately results in anxiety and job dissatisfaction. Concurrent with this nding, previous studies reported, a stressful work environment, increased rate of a medication error and decreased quality of care provided to patients (35,36). Some studies have highlighted that in Egypt, nurses and pharmacists were exposed to hazardous drugs for cancer treatment, and also in Iran, nurses showed changes in their mitochondrial parameters and there was cytotoxicity of their lymphocytes due to exposure to chemotherapy inhalation (5,13).…”
Section: Discussionmentioning
confidence: 77%
“…This ultimately results in anxiety and job dissatisfaction. A stressful work environment, increased rate of a medication error, and decreased quality of care provided to patients (35,36). The pediatric oncology nurses in this current study, experienced perceived tendency that they could contract cancer as a result of caring for children with cancer.…”
Section: Discussionmentioning
confidence: 78%
“…In pediatric oncology, a specialty where care is approached with a family-centered focus, different stressors and challenges arise for staff who take care of the patient as well as the family. For example situations regarding communicating prognostic-related communication (Newman et al, 2018), palliative or end-of-life concerns (Sawin et al, 2019), reviewing the transition between hospital and home (Branowicki et al, 2016), and encountering difficult families (Gallagher & Gormley, 2009) are some of the unique areas a pediatric hematology/oncology nurse encounters. Having a HART presence to help with these challenges was a benefit for staff.…”
Section: Discussionmentioning
confidence: 99%